ANALISIS PENERIMAAN PRODUK BARU PADA BISNIS ECERAN DI DKI JAKARTA - Wahyuningsih Wahyuningsih (Universitas Trisakti, 2004)
The main objective of this research is to analyze the underiying factors of new product adoption decision by retailers. This is important to the companies as they can set appropriate strategies in managing their supply chains, and therefore, they can improve their business performance. The result shows that there are ten main components as underlying factors of new product adoption decision by retailers: new product introduction strategy, purchasing pressure, flexible response, fast response, product reliability, producer's incentives, competitive price, profitability, producer's image, and rivalry internsity.